Tingkat Regulasi Emosi Berdasarkan Jenis Kelamin Siswa Kelas X di SMAN 9 Semarang - Fandila, Thasya Umy; Suhendri (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Adolescence is a phase characterized by behavioral and emotional development. Adolescents often experience erratic emotional fluctuations. This is common among high school children. Adolescents are considered emotionally mature when they can anticipate and control their emotional reactions, rather than reacting impulsively without thinking first. In a high school setting, students encounter a variety of conditions and cultures that may not always fit their own. Therefore, it is very important for students to have strong emotion regulation abilities. The purpose of this study is to examine the disparity in emotion control between male and female students in class X SMA Negeri 9 Semarang. This study utilized quantitative methodology. The study was conducted as a survey, with a sample of 396 students in grade X as the data source. The sample size of the study consisted of 180 students. The data collection approach used was an emotion regulation tool based on Gross' framework. Data analysis revealed gender disparities in emotion regulation among students, which showed a marked difference between males and females. The data showed that female students obtained higher mean scores. Higher scores indicate a higher level of proficiency in managing emotions.